A Case Study in the Application of the Systematic Approach to Training in the Logging Industry - Elise Lagerstrom (Safety, 2019)
The purpose of this research was to develop and assess a targeted emergency first-aid and safety training program for professional loggers in Montana. There were two key objectives for the program: (1) participant demonstration of recall and retention of key concepts and (2) improved participant reception in comparison to the previous year’s training program. The Systematic Approach to Training provided the overall model for the development and conduct of the training program. Qualitative and quantitative analyses were used to assess the effectiveness of the training program. The training program was administered to 873 loggers. Pre-, post-, and follow-up examinations were used to assess recall and retention of key learning objectives, while surveys were used to assess learner reception of the updated training program. Post-training survey data indicated increases in training applicability, understanding of learning objectives, and overall course enjoyment of the updated program in comparison to the previous year’s training program. Participants scored significantly higher on the post-training exams, which demonstrated recall of key training objectives. The results obtained by the training evaluation will guide future research and the continued development of the training program to align with ongoing analysis activities and participant suggestions.